Dialogic validation: a discourse analysis for conceptual development within dialogic classroom interaction. Issue 1 (2nd January 2023) - Sybing, Roehl
ABSTRACT: The contemporary literature regarding dialogic classroom interaction has primarily focused on the meaning-making attributes of dialogue while acknowledging but otherwise providing less emphasis to the social dimensions of the learning community and the dialogic resources that students bring to the classroom. As a result, this paper explores the concept of dialogic validation, which an individual expresses in order to lend credibility or value to another's ideas or sociocultural resources. To propose the outlines of dialogic validation, this paper draws on excerpts from an ethnographic study conducted in an EFL (English as a foreign language) classroom to discursively analyse how an L1 (first language) English-speaking teacher facilitates dialogue with his L1 Japanese-speaking students. Through this discourse analysis, a framework will be generated and proposed to identify elements of dialogue that validate and create a classroom space that values and encourages students' contributions to the teaching and learning processes in dialogic interaction.